Diversity of plant resources in the Xuan Nha Nature Reserve, Son La province - Thai, Tran Huy (Academia Journal of Biology, 2012)
The paper reported 1,131 plant species belonging to 650 genera and 189 families in six divisions of higher vascular plants in Xuan Nha Nature Reserve. Of the total, 33 rare and precious species are observed in the Red Data Book of Vietnam, and of those species 11 species are as endangered (EN), 19 species as vulnerable (VU) and 3 species as critical (CR). Based on the use value, these plant resources are diveded into 8 following commodity groups: woody plants (356 species), medicinal plants (400 species), essential oil plants (90 species), oleiferous plants (20 species), tannin and dye producing plants (30 species), fibre plants and rattans (30 species), edible plants (100 species), ornamental plants (45 species). The yield and chemical compositions of there essential oil plants were identified, such as, Cunninghamia konishii, Forkienia hodghisii, Pinus kwangtungensis. Some suitable solutions for conservation of this plant reosources have been recommended, especially for rare and precious plants.